CHARACTER EDUCATION ISLAM FROM THE VIEWS OF IMAM AL-GHAZALI - Nurhikmah, Nurhikmah (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2024)
Character education is a central topic in developing a child's behavior so that they remain well-mannered, virtuous in socializing with other individuals and groups. This type of research uses qualitative research, with a research method namely literature study. Research sources come from researchers' reading of books, articles and existing research. This research approach uses a descriptive analytical approach which is then discussed in depth, analyzed using content analysis techniques so as to obtain results that can be enjoyed through reading articles. The research results showed that the figure of Imam al-Ghazali as a Muslim philosopher spread his knowledge from various fields, especially education, namely character education. There are character education values ​​according to Imam Al-Ghazali, namely: getting closer to Allah SWT. and obtain happiness in this world and the hereafter, reflection, muhasabah, sincerity, patience, gratitude, fear, and hope, generosity, honesty, gentleness, honesty, patience, and simplicity. These character education values ​​can be applied in everyday life, to children at school and at home so that future generations can have noble morals.